Introducing research methodology : a beginner's guide to doing a research project - Flick, Uwe
In the Second Edition of this textbook designed for new researchers, Uwe Flick takes readers through the process of producing a research project. The book gives readers the fundamental data collection and analysis skills that they need for their first project, as well as a good understanding of the research process as a whole. It covers both quantitative and qualitative methods, and contains plenty of real-life examples from the author's own research. The book will help readers to answer questions such as: Why do social research in the first place? How do I develop a researchable question? What is a literature review and how do I conduct one? How could I collect and analyze data? What if I want to do my research online?